Tantangan dan Prospek Pendidikan Berkelanjutan di Era Global: Menuju Masa Depan yang Berkelanjutan - Prakoso, Chiptiono Yoga; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In facing the complex challenges faced by the world today, sustainable education is the main focus. With the aim of preparing society for a sustainable future, this article discusses the problems and prospects of sustainable education in the global era. This article emphasizes the role of education in promoting inclusive, sustainable and solution-oriented development by analyzing the current global context. Equitable access, quality education, community empowerment, and relevant curriculum development are the main challenges in realizing sustainable education. In addition, this article outlines the challenges and opportunities that arise in efforts to support sustainable education, such as technological innovation, cross-sector collaboration, and holistic learning approaches. Thus, this article provides in-depth insight into these difficulties and opportunities. Therefore, this article provides in-depth insight into the challenges and prospects of sustainable education in the global era. It also offers a framework for sustainable and inclusive educational efforts to build a more sustainable future.